Does Socio-structural Context Matter? A Multilevel Test of Sexual Minority Stigma and Depressive Symptoms in Four Asia-Pacific Countries. (December 2019) - Miedema, Stephanie Spaid; Haardörfer, Regine; Keyes, Corey L. M.; Yount, Kathryn M.
In the Asia-Pacific region, individual sexual stigma contributes to elevated rates of depression among sexual minority men. Less well understood is the role of socio-structural sexual stigma despite evidence that social context influences the experience of stigma. We use data from the United Nations Multi-country Study on Men and Violence to conduct a multilevel test of associations between individual- and cluster unit–level indicators of sexual stigma and depressive symptoms among sexual minority men ( n = 562). In the full model, individual-level sexual stigma is not associated with depressive symptoms, although there is significant variation in the association between individual stigma and depressive symptoms across clusters. Contrary to expectation, at the community level, homophobic injunctive norms are negatively associated with depressive symptoms. We discuss the implications for policies, programs, and future research to improve mental health among sexual minority men in the region.